Comparative growth rates of purebird native catfish, Claria macrocephalus gunther and african catfish, clarias gariepinus butcher. - Jarandilla, Sheila marie M.
Catfishes are one of the economically important groups of fresh and brackish water fishes in the world: in many countries, they form a significant part of inland fisheries. Our native catfish, C. macrocephalus, is one of the world's most accepted fish in the country. However, due to its relatively slow growth and poor breeding activity, our native catfish has been rarely used nowadays on aquaculture. This led to the introduction of exotic and faster growing species like the African catfish, C. gariepinus, and Thai catfish, C. batrachus, which resulted to the near extinction of the native species. External morphological characteristics of C. gariepinus show that it is larger in size upon maturity than C. macrocephalus, but very few studies have been made on the comparative growth assessment of the two species., This research is undertaken to determine the growth performance of purebred Clarias macrocephalus and Clarias gariepinus in a 6 - week study using five-week old catfishes. Results showed that for both variables, length and weight, C. gariepinus advances C. macrocephalus from the very beginning of measurement. Computed value for specific growth rates (SGR) showed a decreasing trend for both species. Independent samples t-test showed significant difference throughout the weeks of measurement for both length and weight. However, only on the 6th week did show a significant difference in the weight of both species. Mean body lengths (MBLs) and mean body weights (MBWs) values for C. gariepinus is consistently higher than C. macrocephalus. The test for homogeneity of linear regression for length showed that slopes a and b are not homogenous. However, slpes of linear regression for weight are homogenous.